EKSPLORASI BALUSE TERHADAP KONSEP BANGUN DATAR - Averlin Kristiani Lahagu; Hardi Tambunan; Ruth Mayasari Simanjuntak (LPPM Universitas Nias Raya, 2025)
This study aims to explore the geometric values embedded in the baluse, a traditional shield of the Nias people, through an ethnomathematical approach. The primary focus of this research is to identify the flat shapes reflected in the visual structure of the baluse and to analyze its potential as a learning medium for introducing the concept of two-dimensional shapes at the elementary and secondary school levels. This study employs a literature review method by examining various cultural texts, visual documentation, and previous studies relevant to the fields of ethnomathematics and culturally-based mathematics education. The findings reveal that the baluse visually incorporates flat geometric shapes such as ellipses, circles, and vertical symmetry. This structure holds significant potential as a contextual teaching medium that can enhance students’ understanding of geometric concepts through cultural perspectives. Furthermore, the results reinforce the idea that mathematics learning integrated with local wisdom not only increases student engagement but also contributes to cultural preservation. The study recommends the development of instructional media and classroom experiments based on the baluse to evaluate its effectiveness in educational practice.